Determination of trace rare earth elements in uranium ore samples by triple quadrupole inductively coupled plasma mass spectrometry. Issue 10 (24th August 2021) - Ding, Xiaotong; Bu, Wenting; Ni, Youyi; Shao, Xuepeng; Xiong, Ke; Yang, Chuting; Hu, Sheng
Abstract : A method for the determination of REEs in uranium ore samples by ICP-MS/MS with O2 reaction and mass-shift detection. Abstract : The distribution of rare earth elements (REEs) in nuclear ore samples provided basic and important information for nuclear forensics. A method was developed for the determination of REEs in uranium ore samples by triple quadrupole inductively coupled plasma mass spectrometry (ICP-MS/MS). A simple and reliable chemical procedure was established for the separation of REEs from the uranium matrix before the measurement. Oxygen was introduced into the mass spectrometry equipment as the reaction gas and the formed REE oxides were detected with the mass-shift strategy. The influences of polyatomic interferents on the measurement of REEs, especially the influences of light REE oxides on the measurement of heavy REEs, were significantly suppressed. The method detection limits were below 1 pg mL −1 for all REEs, ensuring the precise and accurate measurement of REEs in small amounts of uranium ore samples. Several geological reference materials were measured for method validation and the obtained results were consistent with the reported values. Finally, the concentrations of REEs in six types of uranium ore sample were determined. The distribution patterns of REEs in the same type of uranium ore sample were consistent, while those of REEs in different types of uranium ore sample varied significantly. The results further suggested that REE distribution patterns could be used as fingerprints for source identification of related nuclear materials.